2009
DOI: 10.3892/or_00000306
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of human colonic tumor-derived endothelial cells (HCTEC) and normal colonic microvascular endothelial cells (HCMEC): Hypoxia-induced sVEGFR-1 and sVEGFR-2 levels

Abstract: Abstract. Colorectal carcinoma growth and progression is dependent on the vasculature of the tumor microenvironment. Tumor-derived endothelial cells differ functionally from their normal counterpart. For this reason we isolated microvascular endothelial cells from human colon cancer tissue (HCTEC) and compared them with endothelial cells from normal colonic tissue (HCMEC) of the same donor. Since hypoxia is a universal hallmark of carcinomas, we examined its effects on HCTEC of five patients in comparison with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Importantly, a hypoxic TME also impacts the regulation of angiogenesis. In this regard it has been shown that angiogenetic feedback loops by soluble VEGFR are compromised in colon cancer-derived TECs, indicating a pro-angiogenetic disposition of TECs (Jayasinghe et al, 2009). Lastly, a hypoxic micro-milieu affects protein glycosylation and may therefore impact immune cell migration to the tumor and signaling cascades within the TME (Chandler et al, 2019).…”
Section: Tecs Are Highly Proliferative Exhibit Abnormal Gene Expressmentioning
confidence: 99%
“…Importantly, a hypoxic TME also impacts the regulation of angiogenesis. In this regard it has been shown that angiogenetic feedback loops by soluble VEGFR are compromised in colon cancer-derived TECs, indicating a pro-angiogenetic disposition of TECs (Jayasinghe et al, 2009). Lastly, a hypoxic micro-milieu affects protein glycosylation and may therefore impact immune cell migration to the tumor and signaling cascades within the TME (Chandler et al, 2019).…”
Section: Tecs Are Highly Proliferative Exhibit Abnormal Gene Expressmentioning
confidence: 99%
“…This mechanism of protein ectodomain shedding by transmembrane proteases has recently emerged as a key posttranslational regulator of several growth factor receptors involved in angiogenesis [6971]. Although sVEGFR-2 concentrations in cell lysates of human colonic microvascular endothelial cells are reduced in response to hypoxia [72,73], it is unlikely that the decreased plasma sVEGFR-2 concentrations in women with fetal death results from a response of vascular endothelial cells against local hypoxic insults.…”
Section: Discussionmentioning
confidence: 99%
“…Although we know the tumor cells we used express TLR4, we believe that in our system LPS is probably acting on immune cells, particularly on the DCs that infiltrate the tumor site, rather than on the tumor cells, because when LPS was given along with tumor cells, even though the B16F10 cells were in direct contact with LPS, the tumor still grew, indicating absence of direct toxic effects of LPS over the melanoma cells. A study that observed toxic effects of LPS over tumor cells attributed such effects to indirect toxicity over endothelial cells [41,42] rather to direct effects over the tumor cells.…”
Section: Discussionmentioning
confidence: 99%